2014
DOI: 10.1371/journal.pone.0088302
|View full text |Cite|
|
Sign up to set email alerts
|

Pristane-Induced Arthritis Loci Interact with the Slc11a1 Gene to Determine Susceptibility in Mice Selected for High Inflammation

Abstract: AIRmax (maximal inflammation) and AIRmin (minimal inflammation) mice show distinct susceptibilities to pristane-induced arthritis (PIA). The Slc11a1 gene, which regulates macrophage and neutrophil activity, is involved in this infirmity. AIRmaxSS mice homozygous for the non-functional Slc11a1 S (gly169asp) allele obtained by genotype-assisted crosses from AIRmax and AIRmin mice are more susceptible than mice homozygous for the Slc11a1 resistant (R) allele. The present work sought to identify the quantitative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…moreover, it has been reported that the D543n snP apparently confers protection against Mycobacterium tuberculosis reactivation in Cambodian patients infected with HIV (p = 0.04; oR: 0.21) 25 , an association that was not observed in Indian patients 23 . all these data suggest that the D543n SLC11A1 variant has a complex role in the susceptibility to inflammatory and infectious disease, with a relevant interaction with the genetic background of individuals studied 26 .…”
Section: Resultsmentioning
confidence: 80%
“…moreover, it has been reported that the D543n snP apparently confers protection against Mycobacterium tuberculosis reactivation in Cambodian patients infected with HIV (p = 0.04; oR: 0.21) 25 , an association that was not observed in Indian patients 23 . all these data suggest that the D543n SLC11A1 variant has a complex role in the susceptibility to inflammatory and infectious disease, with a relevant interaction with the genetic background of individuals studied 26 .…”
Section: Resultsmentioning
confidence: 80%
“…The congenic strain BALB.D1-1 contains a genomic fragment flanked by markers D1Mit55 and D1Mit209 from DBA/1 in BALB/c background [ 20 ]. We first examined the similarities of whole genome gene expression of BALB.D1-1 to the other four strains of mice.…”
Section: Resultsmentioning
confidence: 99%
“…Because the BALB.D1-1 is deficient in IL-1 receptor antagonist protein (IL-1RA), its expression profile is more similar to the two knockout strains, -/- DBA/1 -/- and BALB/c -/- , than to the wild type strains, BALB/c and DBA/1. Because of the insertion of a fragment from DBA/1, BALB.D1-1 acts similar to -/- DBA/1 -/- , showing resistance to spontaneous arthritis [ 20 ] with a gene expression profile resembling the -/- DBA/1 -/- . However, because BALB.D1-1 is on the BALB/c background, it is least related to DBA/1 with the R value of 0.976964.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This gene is also involved in inflammatory autoimmune diseases [72] and seems to interact with other genes to modulate this phenotype [73], as could be the case with T. cruzi infection in mice selected for acute inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%